Theoretical Explanations of Environmental Motivations and Expectations of Clients on Green Building Demand and Investment. (30th January 2015) - Joachim, Onuoha Iheanyichukwu; Kamarudin, Norhaya; Aliagha, Godwin Uche; Ufere, Kalu Joseph
Abstract: In building industry, green demand and investment creates a positive footprint on the environment. However, these environmental opportunities have not been adequately harnessed and explored by Clients of green building apparently because of poor understanding of the motivating drivers and benefits accruing from green building demand and investment. The decision to demand for or invest in green building is influenced by certain environmental motivating drivers and expectations which have not been fully examined by researchers and not well understood by stakeholders. Based on the Theory of Planned Behaviour (TPB) and Theory of Value Belief Norm (VBN) explanations, this study focused on the Clients, purchasers and users' motivations and intentions to go for green building. Based on the reviewed theories, we hypothesized that environmental motivations and expectations for green building demand and investment are embedded in the environmental quest for protection of eco-system and bio-diversity, improvement of water and air quality, reduction of solid waste, conservation of natural resources, reduction of societal costs of landfill creation and maintenance, minimization of site impact and reduction emission to air and enhanced energy efficiency. However, the predictive validity of these propositions depends on the client's beliefs, values, social pressure, and perceived behavioural control.